The dmc1 Mutant Allows an Insight Into the DNA Double-Strand Break Repair During Meiosis in Barley (Hordeum vulgare L.) - Szurman-Zubrzycka, Miriam; Baran, Brygida; Stolarek-Januszkiewicz, Magdalena; Kwaśniewska, Jolanta; Szarejko, Iwona; Gruszka, Damian (Frontiers in Plant Science, 2019)
Meiosis is a process of essential importance for sexual reproduction, as it leads to production of gametes. The recombination event (crossing-over) generates genetic variation by introducing new combination of alleles. The first step of crossing-over is introduction of a targeted double-strand break (DSB) in DNA. DMC1 (Disrupted Meiotic cDNA1) is a recombinase that is specific only for cells undergoing meiosis and takes part in repair of such DSBs by searching and invading homologous sequences that are subsequently used as a template for the repair process. Although role of the DMC1 gene has been validated in Arabidopsis thaliana, a functional analysis of its homolog in barley, a crop species of significant importance in agriculture, has never been performed. Here, we describe the identification of barley mutants carrying substitutions in the HvDMC1 gene. We performed mutational screening using TILLING (Targeting Induced Local Lesions IN Genomes) strategy and the barley TILLING population, HorTILLUS, developed after double-treatment of spring barley cultivar ‘Sebastian’ with sodium azide and N-methyl-N-nitrosourea. One of the identified alleles, dmc1.c, was found independently in two different M2 plants. The G2571A mutation identified in this allele leads to a substitution of the highly conserved amino acid (arginine-183 to lysine) in the DMC1 protein sequence. Two mutant lines carrying the same dmc1.c allele show similar disturbances during meiosis. The chromosomal aberrations included anaphase bridges and chromosome fragments in anaphase/telophase I and anaphase/telophase II, as well as micronuclei in tetrads. Moreover, atypical tetrads containing three or five cells were observed. A highly increased frequency of all chromosome aberrations during meiosis have been observed in the dmc1.c mutants compared to parental variety. The results indicated that DMC1 is required for the DSB repair, crossing-over and proper chromosome disjunction during meiosis in barley.